Early Venous Thromboembolism Chemoprophylaxis After Traumatic Intracranial Hemorrhage. Issue 6 (18th July 2017) - Frisoli, Fabio A; Shinseki, Matthew; Nwabuobi, Lynda; Zeng, Xiaopei L; Adrados, Murillo; Kanter, Carolyn; Frangos, Spiros G; Huang, Paul P
Abstract: BACKGROUND: Venous thromboembolism is a common complication of traumatic brain injury with an estimated incidence of 25% when chemoprophylaxis is delayed. The timing of initiating prophylaxis is controversial given the concern for hemorrhage expansion. OBJECTIVE: To determine the safety of initiating venous thromboembolic event (VTE) chemoprophylaxis within 24 h of presentation. METHODS: We performed a retrospective analysis of patients with traumatic intracranial hemorrhage presenting to a level I trauma center. Patients receiving early chemoprophylaxis (<24 h) were compared to the matched cohort of patients who received heparin in a delayed fashion (>48 h). The primary outcome of the study was radiographic expansion of the intracranial hemorrhage. Secondary outcomes included VTE, use of intracranial pressure (ICP) monitoring, delayed decompressive surgery, and all-cause mortality. RESULTS: Of 282 patients, 94 (33%) received chemoprophylaxis within 24 h of admission. The cohorts were evenly matched across all variables. The primary outcome occurred in 18% of patients in the early cohort compared to 17% in the delayed cohort ( P = .83). Fifteen patients (16%) in the early cohort underwent an invasive procedure in a delayed fashion; this compares to 35 patients (19%) in the delayed cohort ( P = .38). Five patients (1.7%) in our study had a VTE during their hospitalization; 2 of these patients received early chemoprophylaxis ( P = .75). The rate of mortality from all causes was similar in both groups. CONCLUSION: Early (<24 h) initiation of VTE chemoprophylaxis in patients with traumatic intracranial hemorrhage appears to be safe. Further prospective studies are needed to validate this finding.